2009
DOI: 10.1093/carcin/bgp240
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavins target Fas/caspase-8 and Akt/pBad pathways to induce apoptosis in p53-mutated human breast cancer cells

Abstract: The most common alterations found in breast cancer are inactivation or mutation of tumor suppressor gene p53. The present study revealed that theaflavins induced p53-mutated human breast cancer cell apoptosis. Pharmacological inhibition of caspase-8 or expression of dominant-negative (Dn)-caspase-8/Fas-associated death domain (FADD) partially inhibited apoptosis, whereas caspase-9 inhibitor completely blocked the killing indicating involvement of parallel pathways that converged to mitochondria. Further studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 53 publications
6
45
0
Order By: Relevance
“…More than 98% of the non-adherent population was found to be CD16-negative, among which Ͼ92% were characterized by Wright staining (34). The cells were routinely maintained in complete DMEM or RPMI 1640 at 37°C in a humidified incubator containing 5% CO 2 (36). Cells were allowed to reach confluence before use.…”
mentioning
confidence: 99%
“…More than 98% of the non-adherent population was found to be CD16-negative, among which Ͼ92% were characterized by Wright staining (34). The cells were routinely maintained in complete DMEM or RPMI 1640 at 37°C in a humidified incubator containing 5% CO 2 (36). Cells were allowed to reach confluence before use.…”
mentioning
confidence: 99%
“…For whole cell lysates, cells were resuspended and homogenized in buffer (100 mM Tris-Cl, pH 7.4, 300 mM NaCl, 1% NP-40 and 0.25% sodium-deoxycholate). All the buffers were supplemented with protease and phosphatase inhibitor mixtures (Bhattacharyya et al, 2007;Lahiry et al, 2010). For direct western blot analysis, the cell lysates or the particular fractions were separated by SDSpolyacrylamide gel electrophoresis, transferred to nitrocellulose membrane and probed with specific antibodies, for example, anti-p53, -p63, -p73, -E6, -E7, -p21, -Bax, -PUMA, -ATM, -p-p38MAPK, -p38MAPK, -p-Ser-15-p53, -p-Ser-46-p53, -Cox-2, -Ub, -caspase-3, produced from Santa Cruz (Santa Cruz, CA, USA), thereafter the immunoblots were visualized by chemiluminescence.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Equal protein loading was confirmed with a-actin/ Histone-H1/MnSOD antibody (Santa Cruz). For the determination of direct interaction between two proteins, co-immunoprecipitation technique was employed (Bhattacharyya et al, 2007;Lahiry et al, 2010). Cox-2 and p53 reciprocal co-IP and p53-ubiquitin interaction were performed using cell lysates prepared in Nonidet P-40 (1%) lysis buffer containing protease inhibitors.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Thus, these results suggest that EGCG-triggered apoptosis is involved in the decrease of the protein levels in HSP27 and p-AKT in TSGH-8301 cells. It has been reported that the pro-apoptotic protein BAD, a member of the Bcl-2 family, is rendered inactive when the phosphorylated serine/threonine protein kinase p-AKT converts p-BAD and BAD (52,53). To investigate the downstream effectors, we traced the phosphorylation status of BAD and also assessed the protein levels of Bcl-2 family, including Bcl-2, Bax and BAD in EGCG-treated TSGH-8301 cells with 0, 50, 75 and 100 µM for 24-h exposure.…”
Section: Egcg Alters Hsp27 P-akt Bcl-2 Bax Bad and P-bad Protein mentioning
confidence: 99%